Power Added Efficiency Enhancement in a 2.4 GHz Class E Power Amplifier in 0.13µm CMOS Technology - Hemad Heidari Jobaneh (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Power-Added-Efficiency (PAE) is one of the most significant factors by which the performance of a Power Amplifier (PA) can be scrutinized. A new approach to increase PAE is proposed in this paper. Plus, the trade-off between increasing VDD for more output power and more PAE is examined. In addition, new and precise calculations for both output voltage and output power are achieved. Furthermore, the concept of using an equivalent circuit of a transformer is described to justify the new way to increase PAE. The designed Power Amplifier (PA) operates at 2.4GHz. The simulation is performed by Advanced Design System (ADS) and MATLAB. Plus, the TSMC 0.13 µm CMOS process is utilized to fulfil the procedure. The class E PA is designed to gain two different objectives, including more output power and more PAE. With VDD= 1.18 V the output power is 19.52 dBm and PAE is 68.5 %. Ultimately, with VDD=4.4 V the output power is 31.24 dBm and PAE is 62.7 %.